Determination And Evaluation Of The Minimum Allowable Train Headway Value At The Coordinate Traffic Control Method - et. al., Aikumbekov Muslim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, there has been a steady increase in the volume of traffic. According to experts ' forecasts, the demand for product transportation will continue to increase. Meanwhile, the supply for the capacity of the lines is actually exhausted. Therefore, the most important task of railway transport in the near future will be to increase the carrying capacity and capacity.Increasing the carrying capacity of railway transport can be achieved by: increasing the average speed of trains, building additional tracks, increasing the length and weight of freight trains, reducing inter-train intervals, and organizational measures. To increase the average speed of trains, it is necessary to improve the quality of track maintenance and rolling stock, in addition, certain sections of the track will need to be reconstructed. These measures, including the construction of additional tracks, are long-term and will lead to significant material costs. Increasing the length and weight of freight trains leads to an increase in the number of accidents.The most effective way to increase the carrying capacity is to reduce the inter-train intervals in conjunction with a number of organizational measures.With the coordinate method of interval control, the programs and algorithms obtained on the basis of mathematical models must guarantee the safety of trains with minimal intervals.This fact confirms the need to conduct a set of studies in the field of methodology for ensuring safety and organization of train traffic by clarifying existing and developing new mathematical models of train movement in relation to the specifics of the coordinate method of interval regulation.